Castilian and Others: The Language Situation in Today’s Spain - A. N. Kozhanovsky (Ибероамериканские тетради, 2024)
The Spanish/Castilian language was dominant in Spain during the Franco era, whereas the country’s other regional languages were disenfranchised, which was commonly seen in the Soviet Spanish studies as the most obvious example of non-Castilian-speaking «minority peoples» being oppressed. Therefore, as regional languages were granted the status of «co-official languages» in 1978, Soviet researchers deemed it the most appropriate solution that would help to avoid the «language conflict», reduce ethnic tensions and make regional separatists’ demands groundless. The past four decades of democratic development have shown that the state and status of Spain’s languages, as well as the relations of their speakers remain a pressing issue, with the language situation becoming much more complex and diverse. The authorities of bilingual autonomous communities have started to practice several «language policy» models, first and foremost in education. According to critics, local authorities promote these policies to eliminate Spanish from schooling in order to «linguistically reprogram» the local population and isolate it from the Spanish cultural and historical heritage. In general, there is a substantial difference between the administrative and legal statuses of Spain’s co-official languages and the country’s current language situation, which creates a kind of hierarchy based on official and public recognition amid constant exposure to non-linguistic factors.